Optimum design method of a nano-composite radar absorbing structure considering dielectric properties in the X-band frequency range. (January 2015) - Choi, Ilbeom; Lee, Dongyoung; Lee, Dai Gil
Abstract: A radar absorbing structure (RAS) is generally constructed using nano-composites composed of an E-glass/epoxy composite dispersed with carbonaceous conductive particles to improve the electromagnetic (EM) wave absorbing performance. The EM wave absorptance of the RAS is highly dependent on the dielectric properties of the nano-composite. Therefore, an optimum design method for RAS considering the dielectric properties and the EM wave absorbing characteristics should be established. In this study, a theoretical method for the EM wave absorbing characteristics of nano-composite RAS was developed with respect to the dielectric properties of the nano-composites. Based on the theoretical investigation, an optimum design method for the RAS was developed. Then the RAS was constructed with the nano-composite composed of an E-glass/epoxy composite and carbon black and its EM wave absorbing performances were measured and compared to those obtained through theoretical calculations and numerical simulations.